Menetralisasi Cara Pandang Berlebihan antar Ormas Nahdlatul Ulama dan Muhammadiyah di Madura: Suatu Kajian Moderasi Beragama - Hamdani, Hamdani; Al-Humaidy, Mohammad Ali; Efendi, Agik Nur; Maimun, Maimun (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Nahdlatul Ulama and Muhammadiyah mass organizations in Madura are considered to be different mass organizations in the midst of Madurese society. Views like this result in some Madurese people having an exaggerated view of other mass organizations that are different from the ones they follow. The excessive views in question are like views that are often found in public dialogue which then say that other mass organizations are bi'ah organizations, not in line with Islam and so on. The aim of this research is to neutralize excessive views, namely through the concept of Bergama moderation which was initiated by the Ministry of Religion of the Republic of Indonesia (Kemenag RI). The method used in this research is the library research method. The data analysis stage is carried out by searching for data that is appropriate to the research context and the data is presented and analyzed by conveying the data found (descriptive), and the last is the conclusion drawing stage. The results of this research are that the Bergama conception of moderation can be instilled in the community in order to provide a straight understanding of the two mass organizations and to develop moderate thinking without being excessive towards adherents of NU or Muhammadiyah mass organizations. This can be achieved by inserting the concept of religious moderation in education, in the form of special studies on religious moderation or in the form of direct application in society.